Trait Diversity of Pulse Species Predicts Agroecosystem Properties Trade-Offs - Guiguitant, Julie; Vile, Denis; Marrou, Hélène (Frontiers in Plant Science, 2021)
Crop diversity management in agriculture is a fundamental principle of agroecology and a powerful way to promote resilient and sustainable production systems. Pulses are especially relevant for diversification issues. Yet, the specific diversity of legumes is poorly represented in most cropping systems. We used the trait-based approach to quantify the functional diversity of 30 pulses varieties, belonging to 10 species, grown under common field conditions. Our aim was to test relationships between traits, yield, and supporting agroecosystem properties. Our experimental results highlighted trade-offs between agroecosystem properties supported by different combinations of traits. Also, results demonstrated the relevance of leaf nitrogen content (LNC), leaf area ratio (LAR), and reproductive phenology to predict most of the trade-offs observed between agroecosystem properties. A comparison with a previous analysis based on literature data collected in diverse agronomic situations suggested that some traits are more plastic than others and therefore contribute differently to frame legumes diversity depending on the conditions of observation. Present results suggested that the implementation of such trait-based approach would rapidly benefit the selection of species/varieties for specific targeted agroecosystem services provisioning under specific (environmental or management) conditions.